Legal Problems of Over-Indebtedness of Developing Countries. Current Relevance of The Doctrine of Odious Debts. - Frankenberg, Günter (1984)
This paper aims to discuss the part of the debt problem that is mainly composed of credits used for investments of dubious value from a development point of view, working on the basis of the so-called ‘odious debts’ of international law, and their link to the theory and practice of economic development. The purpose of the paper is to contribute to the solution of the current debt problem and its prevention for the future. Its basic assumptions are, firstly, that only by incorporating objective criteria that can be inferred from the international development debate is it possible to avoid an even more catastrophic situation; and, secondly, that the development value of goods exported to the Third World is a risk shared by the supplier and the buyer together.